Desain Tata Kelola Rekam Medis Elektronik Berbasis Teknologi Informasi Dalam Pelayanan Pasien IGD Dengan Metode Agile - Anggriani, Mia; Syahidin, Yuda; Sari, Irda; Sukmawijaya, Jeri (Program Studi Teknik Informatika Universitas Pamulang, 2023)
By seeing that there are still problems related to the governance of emergency room patient services at Al-Ihsan Hospital, the problems that occur are due to the registration system often experiencing errors so that when patients register through the emergency room they experience obstacles. This research focuses on the design of information technology-based electronic medical record governance in emergency room patient services. This research was conducted with the aim of improving the quality of emergency room patient services so that patient information is available quickly and easily accessible by medical personnel in need. Agile method with Extreme Programming type is used to design the system to be made by going through the stages of planning, design, coding and testing. Needs analysis is done by conducting interviews and making direct observations, then designing the system using the Unified Modeling Language (UML). After the design stage is complete, the system testing stage is carried out to ensure that all functions can run as expected. The results of the application of this method show that the information technology-based RME governance system in emergency room patient services with the Agile XP method can design information technology governance well able to speed up the data entry process, improve data accuracy and facilitate data access by personnel. The conclusion obtained with this information system can improve IT governance-based information function services that are useful for increasing flexibility and responsiveness in emergency room services and making it easier for medical personnel to process data.